The Approach of Imam Abdul Hamid ibn Badis to Sufi Methods - Omrani, Belkheir Ahmed (Al-Jami'ah Research Centre, 2023)
This research is about Shaikh Abdul Hamid ibn Badis, the president of the Algerian Association of Muslim Scholars, who led the reformist movement during the French occupation and was one of the leaders of reformation in the Muslim world. The research aims to reveal how the Shaikh dealt with the reality of Sufism and its spiritual authority and broad influence embedded in Algerian society. The author addresses issues within Algerian society during the French occupation, the position of the Shaikh as a man of satire in general, and his relationship with the elders’ zawaya of Sufi methods. The research concludes that the Shaikh followed a middle ground in his dealings. He was clear in his opinions and convictions and expressed them through his writings and articles, while he had good connections with all the elders’ methods. His approach was not to differentiate but to assemble and remove the differences that weakened the society’s resistance towards the French occupation. As the Imam had been wise and advocative, he knew how to win the hearts and attitudes of his society.[Tulisan ini membahas Syaikh Abdul Hamid ibn Badis, Pemimpin Asosiasi Ulama Muslim Aljazair, yang memimpin gerakan reformis pada masa pendudukan Perancis dan merupakan salah satu pemimpin reformasi di dunia Muslim. Penelitian ini bertujuan untuk mengungkap bagaimana sang Syaikh menyikapi realitas Tarekat serta otoritas spiritual dan pengaruhnya yang luas, yang tertanam dalam masyarakat Aljazair. Penulis membahas isu-isu yang terjadi di tengah masyarakat Aljazair selama pendudukan Perancis, posisi sang Syaikh sebagai satir secara umum, dan hubungannya dengan zawiyah-zawiyah Tarekat yang lebih tua. Penelitian ini menyimpulkan bahwa Ibn Badis telah memilih jalan tengah. Pendapat dan keyakinannya jelas, dia mengungkapkannya melalui tulisan dan artikelnya, sementara hubungannya dengan semua zawiyah Tarekat dibina sangat baik. Pendekatannya bukan untuk membeda-bedakan tetapi untuk mengumpulkan dan menghilangkan perbedaan-perbedaan yang melemahkan perlawanan masyarakat terhadap pendudukan Perancis. Karena sang Imam adalah orang yang bijaksana dan advokatif, dia tahu bagaimana memenangkan hati dan sikap masyarakatnya.]